Bovine lactoferrin inhibits Japanese encephalitis virus by binding to heparan sulfate and receptor for low density lipoprotein - Chien, Yu-Jung; Chen, Wei-June; Hsu, Wei-Li; Chiou, Shyan-Song (Virology (New York, N.Y.), 2008)
Lactoferrin is a natural anti-microbial protein which affects Japanese encephalitis virus (JEV) activity. Binding of lactoferrin to cell surface expressed heparan sulfate (HS), one possible receptor for JEV, has been postulated to be the possible mechanism of anti-JEV antiviral activity. In this study, we evaluate the effects of bovine lactoferrin (bLF) against JEV infection in vitro, using both wild-type (WT) and laboratory-adapted strains. bLF inhibited the infectivity of all the JEV strains tested. In particular the infectivity of the HS-adapted JEV strains was strongly reduced, whereas the non HS-adapted JEV strains were inhibited to lesser extent. Using both HS-adapted CJN-S1 and non HS-adapted CJN-L1 viruses, the results showed that bLF inhibited the early events essential to initiate JEV infection, which includes blocking virus attachment to cellular membranes and reducing viral penetration. This anti-JEV activity was the highest using HS-adapted CJN-S1 strain on HS-expressed CHO-K1 cells. Also, binding of bLF to heparin-sepharose blocked JEV binding; and soluble HS attenuated the anti-JEV activity of bLF. The results support the premise that the interaction of bLF with cell surface expressed glycosaminoglycans, in particular the highly sulfated HS, plays an essential role in the antiviral activity of bLF. However, bLF was functional in inhibiting CJN-S1 entry into HS-deficient CHO-pgsA745 cells, and bLF-treated CHO-K1 and -pgsA745 cells also prevented non HS-adapted CJN-L1 virus entry, indicating that a non-HS pathway may be involved in bLF inhibition of JEV entry. The low-density lipoprotein receptor (LDLR), possibly involved in the entry of several RNA viruses, also binds to bLF. We found that both rLDLR and anti-LDLR antibodies reduced the effectiveness of bLF inhibition of JEV infection. This finding provided evidence to suggest that cell surface-expressed LDLR may play a role in JEV infection, especially for non HS-adapted strains.